Commentary on the Resolution of the Court of Justice of EU C-311/18 (Schrems II), 16th July 2020 (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2021)
Companies stablished in the European Union (EU) which used to transfer personal data of European citizens to American entities used to do so using the Privacy Shield as a legal framework, a decision of the European Commission that guaranteed the existence of an adequate level of data protection in the United States. However, in July 2020 the European Court of Justice invalidated this decision, creating uncertainty in many of these companies. This commentary aims to analyze what the main consequences of this ruling are and what alternatives EU companies now have.
Keywords: Privacy shield; standard data protection clauses; personal data; Schrems; transfers; European Union; United States; level of protection